Sosialisasi Pemanfaatan Sistem Informasi Manajemen Rumah Sakit (SIMRS) terhadap Pengolahan Data pada Laporan Eksternal dan Internal di RSU Imelda Pekerja Indonesia Medan Tahun 2025 - Sitorus, Mei Sryendang; Valentina, Valentina; Liem, John Barker; Ardanta, Yanda; Hutasoit, Theresia; Daeli, Cosmas Samuel; Hasibuan, Ali Sabela; Ritonga, Zulham Andi; Erlindai, Erlindai; Christy, Johanna (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Hospital Management Information System (HMIS) at Imelda Pekerja Indonesia General Hospital has been in place since 2015; however, the system has not yet been utilized as the primary source for data processing.Reporting staff sometimes still process data manually collected from each service unit.External reports are mandatory reports submitted by every hospital to the Health Office. Internal reports are used for the hospital’s internal purposes.The implementation method of this community service activity consisted of socialization on the utilization of SIRS for data processing, reviewing the Standard Operating Procedure (SOP) for Reporting and creating a checklist of data requirements for reports.The socialization was provided to all 16 medical record officers in the Medical Records Unit using discussion, lecture, and question-and-answer methods. The results of this activity are expected to improve the staff’s knowledge regarding the utilization of HMIS for data processing in reports at hospital.This activity was successfully carried out due to the cooperation and support of all implementing team members and hospital team.However, the common obstacles faced by staff include network and application disruptions, which hinder the data processing for hospital reporting. Therefore, improving network stability within the system is necessary to ensure that the reporting process can run more effectively and efficiently.